2021
DOI: 10.1097/spv.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Menopausal Status on Uropathogen Prevalence and Antimicrobial Resistance Profiles

Abstract: Objectives The unique factors associated with urinary tract infections (UTIs) in postmenopausal (PMP) women have been significantly less investigated as compared with premenopausal (PreMP) women. Our objective was to compare the prevalence of uropathogens and antibiotic resistance patterns between PreMP and PMP women with UTIs. Methods This was a cross-sectional analysis of PreMP and PMP women treated for a UTI in a urogynecologic practice between Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Together, these factors increase the chance that microbes with uropathogenic capability establish residence in the vagina. 6 There are mixed results in the literature regarding the impact of menopausal status on uropathogen prevalence and antimicrobial resistance profiles 7,8 and further investigation is necessary.…”
mentioning
confidence: 99%
“…Together, these factors increase the chance that microbes with uropathogenic capability establish residence in the vagina. 6 There are mixed results in the literature regarding the impact of menopausal status on uropathogen prevalence and antimicrobial resistance profiles 7,8 and further investigation is necessary.…”
mentioning
confidence: 99%
“…Additionally, our results surrounding proportion of uropathogens are consistent with the literature, despite a small sample size. Studies from our institution that evaluated urine cultures in symptomatic UTI patients revealed similar uropathogens with high resistance patterns, especially in women with rUTI [ 10 , 11 ]. Additional research to compare traditional urine cultures with the multiplex PCR home UTI test is necessary along with prospective studies to determine symptomatic response after treatment.…”
Section: Discussionmentioning
confidence: 99%